The Many Misspellings of Albuquerque: A Comment on 'Sorting or Steering: The Effects of Housing Discrimination on Neighborhood Choice' - Shi Chen; Areez Gangji; Sunny Karim; Anthony McCanny; Matthew D. Webb (Institute for Replication (I4R), 2024)
This comment revisits the analysis in Christensen and Timmins (2022). We identify two critical errors used in the original analysis, one with the data and the other with coding. When either error is corrected several major results in the paper change, either in statistical significance or in effect size. The data error is a result of including fixed effects for the string variable 'city'. The raw variable is case sensitive and has many spelling mistakes. The coding error involves assigning a value of zero for the variable "of color" to both individuals identified as 'white' and as 'other' in the raw data. The level of clustering in the paper is also arguably too fine. Many of the results are not robust to clustering at the city level, as opposed to the subject pair level. In total, we affirm the authors' overarching claim of substantial and nuanced housing discrimination against racial minorities generally, and African Americans in particular; however, the effect sizes and significance are generally (although not always) smaller than the original authors findings. Additionally, there are several instances where the effects of discrimination on African Americans are no longer statistically significant but the effect of discrimination on Hispanics becomes significant.
Keywords: 330